2019
DOI: 10.1371/journal.pone.0219432
|View full text |Cite
|
Sign up to set email alerts
|

Genotype x environment interaction and genetic gain for grain yield and grain quality traits in Turkish spring wheat released between 1964 and 2010

Abstract: The study was conducted to determine the effects of genotype (G), environment (E), their interaction (GEI) and genetic gain on yield and grain quality traits in Turkish spring wheat cultivars released between 1964 and 2010. We conducted a multi-environment trial at three testing locations: Adana, Adapazarı, and Izmir, during the 2009, 2011 and 2013 cropping seasons and tested 35 cultivars released by the respective breeding programs. Allelic variations of high and low molecular weight glutenin subunits (HMW-GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 49 publications
9
37
0
3
Order By: Relevance
“…It was observed that the effect of environment on the fiber content of corn grains was stronger as compared to the genotype. This finding is in accordance with other scientific studies [18,37].…”
Section: Quality Characteristics Of Harvested Corn Grainssupporting
confidence: 94%
See 2 more Smart Citations
“…It was observed that the effect of environment on the fiber content of corn grains was stronger as compared to the genotype. This finding is in accordance with other scientific studies [18,37].…”
Section: Quality Characteristics Of Harvested Corn Grainssupporting
confidence: 94%
“…The protein content was mainly affected by the environment rather than the genotype. This finding is in accordance with other scientific studies [18,35,36]. The protein content of corn grain is illustrated the quality of corn flour and is a desirable trait for the food industry.…”
Section: Quality Characteristics Of Harvested Corn Grainssupporting
confidence: 92%
See 1 more Smart Citation
“…Genetic variation in GY in wheat has previously been associated with green canopy area duration under drought in wheat (41,(47)(48)(49)(50), sorghum (51). The role of senescence dynamics -start, end and rate of senescence -is important as they relate to grain filling duration and post-anthesis water and N uptake (50,52). Under irrigated conditions, GY was associated positively with senescence start (SenSt) in 2018.…”
Section: Associations Between Canopy Senescence Traits and Responses mentioning
confidence: 99%
“…Canadian wheat cultivars have properties that meet the specific end‐use requirements (Canadian Grain Commission, ). However, processing and end‐use quality are affected by the environment (Malik, Kuktaite, & Johansson, ; Nehe et al, ), which can alter the flour attributes and alter the end‐product quality. Dough improvers can alleviate flour quality deficiencies in bread‐making, to consistently produce desirable quality end‐products to meet customer preferences.…”
Section: Introductionmentioning
confidence: 99%